2015
DOI: 10.1248/bpb.b14-00539
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of Bee Venom on Methamphetamine-Induced Cellular Activities in Prefrontal Cortex and Nucleus Accumbens in Mice

Abstract: Our previous studies demonstrated that subcutaneous injection of bee venom (BV) into the Zusanli (ST36) acupuncture point, namely BV acupuncture, dose-dependently prevents conditioned place preference (CPP) induced by repeated injection of methamphetamine (METH) in mice. To expand on our observations, the present study was designed to determine the suppressive mechanisms of BV acupuncture in the development of METH-induced CPP by evaluating the changes in expression of ΔFosB, phosphorylated extracellular signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…However, our data extend to the mPFC, the results of earlier drug-induced place-conditioning studies in which systemic pretreatment with ERK inhibitors [58][59][60][61][62] or targeted ERK inhibition within the nucleus accumbens [51,63] were reported to inhibit drug-induced place-preference in rodents. The present data also align with other studies linking the efficacy of potential anti-addiction medications at blocking CPP with a reduction in phospho-ERK expression within mPFC, e.g., [53,64].…”
Section: Local Inhibition Of Mpfc Erk Phosphorylation Eliminates An Established Ma-cpp Phenotypesupporting
confidence: 90%
“…However, our data extend to the mPFC, the results of earlier drug-induced place-conditioning studies in which systemic pretreatment with ERK inhibitors [58][59][60][61][62] or targeted ERK inhibition within the nucleus accumbens [51,63] were reported to inhibit drug-induced place-preference in rodents. The present data also align with other studies linking the efficacy of potential anti-addiction medications at blocking CPP with a reduction in phospho-ERK expression within mPFC, e.g., [53,64].…”
Section: Local Inhibition Of Mpfc Erk Phosphorylation Eliminates An Established Ma-cpp Phenotypesupporting
confidence: 90%
“…The increase of pERK, pElk-1, pCREB, and/or ΔFosB protein expression in the CPu, NAc or PFC is related to METH-induced CPP 180,181 . Specifically, the acquisition of CPP and pERK induction in the NAc by METH-CPP require D1-R but not NMDA-R activation.…”
Section: Erk Signaling and Drug Addictionmentioning
confidence: 96%
“…It has been reported that inflammatory factors are induced by ERK ( 39 ). METH exposure significantly increases the activity of ERK ( 40 , 41 ). Several lines of evidence have shown that ERK activation might activate NF-κB ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 98%